FLOW CYTOMETRIC DETECTION OF HAPLOIDS, DIPLOIDS AND MIXOPLOIDS AMONG THE ANTHER-DERIVED PLANTS IN INDICA RICE (ORYZA SATIVA L.) - Mayakaduwa, D.M.R.G.; Silva, T.D. (Department of Plant Sciences, Faculty of Science, University of Colombo, 2019)
Plants regenerated from anther culture of the Indica rice var. ‘At 303’ were analyzed using flow cytometry and morphological parameters were studied. Plant analysis carried out using flow cytometry confirmed that 40% of the plants were haploid, 50% were diploid and 10% were mixoploid (haploid/ diploid). Stomatal measurements (length, width and density) were obtained for plants regenerated from anther culture and compared with measurements from diploid plants derived from seeds which served as the standard reference material. Smaller cell size and higher cell density are indications of lower ploidy status. The data showed that the cell size was significantly lower (p≤0.05) in all anther-derived plants compared to diploid seed-grown plants. However, stomatal density was significantly higher (p≤0.05) in only two of the plants (plant nos. 11 & 12) regenerated from anther culture compared to seed-grown plants. Cluster analysis of the stomatal data as well as other morphological and reproductive trait measurements, indicated that only the latter two plants in this group were true haploids (33%). Thus, the ploidy estimates from stomatal and other morphological trait analyses corroborated the flow cytometric evidence. That is, both types of analyses determined that less than half of the total regenerants were haploid. Anther culture is performed with the intention of regenerating haploid or doubled haploid plants to develop homozygous lines. Therefore this study revealed that, it is important to improve further, the efficiency of regenerating haploids or dihaploids through anther culture in Indica rice for the technique to be practically viable.
Keywords: Anther culture, Flow cytometry, Haploids, Diploids, Mixoploids